ANALISIS HUBUNGAN TINGKAT KECEMASAN MATEMATIKA DENGAN HASIL BELAJAR MAHASISWA - Endang Istikomah; Ratu Sarah Fauziah; Edi Irawan; Mahmudin Mahmudin (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2018)
This study aims to analyze the relationship between mathematical anxiety, and students' mathematics learning outcomes. This research is a correlational study using linear correlation and multiple linear correlation. Data analysis was carried out using the SPSS 21 program. Data was taken from 113 respondents who were students of the Mathematics Education Study Program 2017/2018 school year. The independent variable in this study is mathematical anxiety (X) and the dependent variable is students' mathematics learning outcomes (Y). The results of the study showed that there was a relationship between mathematics anxiety and the mathematics learning outcomes of the sixth semester students in the MNA subject with a significance level of 0. 001 and the R value was 0.299.